Extraction of natural color component from the bark of Belleric myrobalan (Terminalia bellerica): Kinetic and adsorption studies - Vinod, Konaghatta Narayanachar; Puttaswamy, Puttaswamy; Gowda, Kurikempanadoddi Ninge; Sudhakar, Rajagopal (European Journal of Chemistry, 2010)
Baicalein, a trihydroxy flavone from the bark of Terminalia bellerica was identified as a natural colorant. The potential of the natural color component on silk yarn was tested. Its properties of color fastness with regard to light, washing and crocking were investigated and found to be satisfactory. Thermodynamic parameters were evaluated. The positive value of enthalpy of dyeing suggests the endothermic nature of dyeing and the negative entropy implies that the dye molecules are orderly arranged on silk. The positive value of free energy confirms the affinity between the dye molecules and the protein content of silk. Further, adsorption studies were carried out to determine the best fit isotherm model for the present dyeing system. The Langmuir isotherm model fitted the experimental data very well with a relatively high regression coefficient compared to the Freundlich and Tempkin-Pyzhev isotherm models. In conclusion, the Terminalia bellerica bark can be used as a potential source of natural dye for silk.